2022
DOI: 10.3389/fimmu.2022.837376
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Total Tau Protein Correlates With Longitudinal, Progressing Cognitive Dysfunction in Anti-Neural Autoantibody-Associated Dementia and Alzheimer’s Dementia: A Case–Control Study

Abstract: BackgroundNeural autoantibody-associated dementia (NABD) is an increasing phenomenon in memory clinics with a high impact on later therapy. Biomarkers are lacking that differentiate this type of dementia from neurodegenerative dementia such as Alzheimer’s dementia (AD). Our aim is to analyze neurodegeneration markers and their relationship to progressing cognitive dysfunction in NABD and AD to test for tools differentiating these two forms of dementia prior to neural autoantibody testing.MethodsIn our retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Thus, in our delirium patients, it is unclear if the autoantibodies present are associated with the dementia condition or the delirium, and more research is necessary to clarify this question. Neural autoantibody- associated dementia ( 1 , 3 5 ) is a growing field in immunopsychiatry that deserves further attention. In an earlier study we showed that a substantial proportion of patients with cognitive impairment reveal an association with neural autoantibodies ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in our delirium patients, it is unclear if the autoantibodies present are associated with the dementia condition or the delirium, and more research is necessary to clarify this question. Neural autoantibody- associated dementia ( 1 , 3 5 ) is a growing field in immunopsychiatry that deserves further attention. In an earlier study we showed that a substantial proportion of patients with cognitive impairment reveal an association with neural autoantibodies ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell membrane-surface ( 11 16 ) and intracellular antibodies ( 17 , 18 ) have been reported in delirium states. Neural autoantibodies occur in cognitive impairment ( 1 , 3 5 ), which is known to be a risk factor for triggering delirium ( 19 ). It thus makes sense to look for autoantibodies especially in patients with delirium and preexisting cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This finding confirms studies that reported AD associated with significantly decreased Aβ42 and a lower ratio Aβ42/40 compared to patients suffering from autoantibody-associated cognitive dysfunction [ 26 ]. Tau enables us to distinguish between AD and autoantibody-associated dementia, since this biomarker is significantly elevated in AD patients [ 27 ]. Another of our studies' findings is that the Ab-p group's neurodegeneration biomarkers did not differ significantly between syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…However, note that as the ptau 181 neurodegeneration biomarker failed to differ significantly between our antibody-positive cohort and AD cohort, this evidence can be interpreted as an indication of axonal neurodegeneration in the antibody-positive group. Elevated ptau 181 in autoantibody-associated psychiatric disorders has been demonstrated [ 27 , [34] , [35] , [36] , [37] ], and should be further validated in large-scale studies, as this is where diagnostic and therapeutic opportunities lie for psychiatric patients. Our finding that psycho-organic syndrome showed the most severe neurodegeneration among syndromes was expected because of its organic component and its overlap with symptoms of neurodegenerative dementia pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This process may lead to the emergence of immune cells producing Ab reacting to surface proteins of intact neurons and other brain cells, as well as peptides and proteins released after their pathological breakdown 38 - 40 . Such autoimmune reaction has been implicated in autoimmune response-related psychosis and schizophrenia 41 , 42 as well as neural autoantibody-associated dementias (NABD) with signs of axonal degeneration 43 , 44 . Quantitative analysis and profiling of Aabs targeting neuronal proteins, may, therefore, provide specific and instructive information on the onset, mechanisms, and severity of brain pathology.…”
Section: Biology Of Aabs With Relevance To Nddsmentioning
confidence: 99%